Characteristics of REPRIEVE Trial Participants Identifying Across the Transgender Spectrum. (9th July 2020) - Smeaton, Laura M; Kileel, Emma M; Grinsztejn, Beatriz; Gardner, Edward M; Starr, Kate; Murry, Melissa L; Desvigne-Nickens, Patrice; Alston-Smith, Beverly; Waclawiw, Myron A; Cooper-Arnold, Katharine; Madruga, José V; Sangle, Shashi; et al.
Abstract: Because persons who identify across the transgender spectrum (PATS) are a key population in human immunodeficiency virus (HIV) yet are underreported in HIV and cardiovascular research, we aimed to characterize this population within the REPRIEVE global clinical trial (n = 7770). Acceptance of gathering gender identity was high (96%). Participation by PATS was 1.7% overall, 2.4% among natal males, 0.3% among natal females, and varied across geographic regions (from 0% in sub-Saharan Africa to 2.3% in High Income Region). Thirty percent of natal male PATS identified other than transgender. Some characteristics differed by gender. Most notably, 38% of natal male PATS receiving gender-affirming treatment had waist circumference >102 cm (compared with ≤25% in other groups). Given that PATS is a key population, HIV research should routinely report trial participation and outcomes by gender in addition to natal sex, to provide the results needed to optimize medical care to PATS.